Nitrided modified silicon negative electrode material and preparation method and application thereof

By preparing a silicon nitride/titanium nitride two-component coating on the surface of the micron silicon negative electrode material, the problems of cracking, crushing and poor conductivity of the silicon negative electrode material due to volume expansion and unstable SEI film are solved, and efficient electrochemical performance and long cycle life are achieved, which is suitable for large-scale commercial applications.

CN119601626AActive Publication Date: 2025-03-11WUHAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411758815.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-11
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Silicon anode material has problems of rupture, crushing and poor conductivity due to volume expansion and unstable solid electrolyte interface (SEI) films in lithium-ion batteries, limiting its large-scale commercial application.

Method used

By preparing a silicon nitride/titanium nitride two-component coating on the surface of micron silicon particles, amorphous silicon nitride is used to form an inorganic-rich SEI film, and providing excellent electron conduction properties through titanium nitride, promoting the porous evolution of the micron silicon negative electrode to form a stable porous structure.

Benefits of technology

It significantly improves the long cycle life and electrochemical properties of silicon negative electrode materials, solves the problems of instability and poor conductivity of SEI films, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601626A_ABST
    Figure CN119601626A_ABST
Patent Text Reader

Abstract

The invention provides a nitriding modified silicon negative electrode material and a preparation method and application thereof, a method for carrying out surface nitriding treatment on micron silicon particles and nano titanium nitride particles is adopted, a silicon nitride / titanium nitride bi-component coating is prepared on the surface of the material by controlling the reaction temperature and time, and the surface property of micron silicon is improved, silicon nitride is in an amorphous state and can participate in formation of an SEI film rich in inorganic matter in the circulation process, the SEI film is complete, compact, good in stability and capable of providing rapid lithium ion diffusion kinetics, titanium nitride can provide excellent electron conduction performance, and the coating promotes evolution of a micron silicon negative electrode to be porous to finally form a stable porous structure. And obvious cracking and pulverization do not occur. The material has high initial coulombic efficiency, high capacity retention ratio, excellent rate capability and cycling stability when being used as a lithium ion battery negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy materials, and specifically relates to a nitrided silicon negative electrode material and a preparation method and application thereof. Background Art

[0002] One of the goals of lithium-ion battery development is to increase energy density. Since the first generation of commercial lithium-ion batteries in 1991, the gram capacity of positive and negative electrode materials has become the key to determining the energy density of batteries. For negative electrode materials, the potential development of graphite negative electrode materials is close to the limit and can no longer meet human needs. Studies have found that silicon has the highest known theoretical specific capacity as a negative electrode material, with a capacity of up to 4200 mAh / g, which is about 11 times that of graphite (theoretical specific capacity 370 mAh / g). In addition, silicon is the second largest element in the earth, easy to obtain and environmentally friendly. At the same time, silicon has a low electrochemical discharge potential, so silicon has the potential to replace graphite to innovate commercial lithium-ion battery negative electrode materials. However, unlike the intercalation reaction mechanism of graphite during lithiation, silicon undergoes an alloying reaction mechanism during lithiation, resulting in a volume expansion of up to 300%, which will cause the material to break and pulverize, and produce an unstable solid electrolyte interface (SEI) film. Silicon also has disadvantages such as poor electronic conductivity and ionic conductivity. These disadvantages limit the large-scale commercial application of silicon negative electrodes.

[0003] Nano-sizing silicon materials and compounding them with other materials (amorphous carbon, graphite, Sn, etc.) is a good way to alleviate the shortcomings of silicon negative electrodes, such as large volume expansion and poor conductivity. However, silicon nanomaterials have low tap density, complex processes, and high costs, making them difficult to manufacture on a large scale. Compared with nano-silicon, micron silicon has the characteristics of low cost and high tap density. Its lower specific surface area can significantly reduce harmful side reactions, thereby increasing the initial and post-cycle coulombic efficiency of the electrode. Modification of micron silicon can improve its long-cycle performance, so micron silicon has more commercial prospects. Summary of the invention

[0004] The present invention provides a method for preparing a nitrided modified micron silicon negative electrode material, and aims to provide a method for preparing a micron silicon negative electrode material with a long cycle life in view of the deficiencies of the prior art. The surface of the micron silicon negative electrode material prepared by the method is a layer of silicon nitride / titanium nitride two-component coating, wherein amorphous silicon nitride can participate in the formation of an inorganic-rich SEI film during the cycle process, the SEI film is complete and dense, has good stability, and can provide fast lithium ion diffusion kinetics, titanium nitride can provide excellent electronic conduction performance, and the coating can promote the micron silicon negative electrode to evolve into a porous structure and finally form a stable porous structure without obvious cracking and pulverization.

[0005] In order to achieve the above object, the present invention adopts the following technical solution: The invention provides a nitrided silicon negative electrode material, which comprises micron silicon particles and nano titanium nitride particles distributed on the surfaces of the micron silicon particles, wherein the surfaces of the micron silicon particles and the nano titanium nitride particles are both coated with an amorphous silicon nitride layer. Furthermore, the particle size of the micron silicon particles is 1-3 um, and the particle size of the titanium nitride particles is 5-30 nm.

[0006] Furthermore, the thickness of the amorphous silicon nitride layer is 5-25 nm.

[0007] The present invention also provides a method for preparing the above-mentioned nitrided silicon negative electrode material, comprising the following steps: 1) Take micron silicon particles and titanium nitride particles and add them to a solvent for ultrasonic dispersion, and then stir them to make them evenly dispersed to obtain a uniform suspension.

[0008] 2) Dry the suspension to obtain micron silicon / titanium nitride mixed powder.

[0009] 3) The mixed powder is placed in a tubular furnace and calcined at high temperature in a nitrogen atmosphere to obtain silicon@silicon nitride / titanium nitride material, that is, a nitride-modified silicon negative electrode material.

[0010] Furthermore, in the step 1), the mass ratio of the micron silicon particles to the titanium nitride particles is 5:1.

[0011] Furthermore, in step 1), the solvent is one or more of water, methanol, ethanol, and NMP.

[0012] Furthermore, in the step 1), the ultrasonication time is 20 min-60 min, and the stirring time is 0.5 h-2 h.

[0013] Furthermore, in the step 3), the high temperature calcination temperature is 1200-1400°C, and more preferably, the high temperature calcination temperature is 1300°C; the high temperature calcination time is 1-30 min, and more preferably, the high temperature calcination time is 5 min.

[0014] Furthermore, in the step 2), the drying temperature is 80-120° C. and the drying time is 20-30 hours.

[0015] The present invention also provides a use of the silicon negative electrode material as described above or the silicon negative electrode material prepared by the method as described above in a lithium ion battery.

[0016] The beneficial effects of the present invention are: 1) Using nitrogen to prepare amorphous silicon nitride, the surface properties of micron silicon are improved to solve the instability problem of repeated generation and rupture of SEI film of silicon negative electrode; 2) The added titanium nitride can maintain structural stability at high temperatures and provide good conductivity for the silicon negative electrode; 3) High reaction efficiency: the surface nitridation of micron silicon particles can be completed in a short time; 4) The operation process is simple, the cost is low, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is a SEM image of the micron silicon negative electrode material (denoted as Si@SiNx / TiN) prepared in Example 1; Figure 2 TEM image of the micron silicon negative electrode material (denoted as Si@SiNx / TiN) prepared in Example 1; Figure 3 XRD pattern of the micron silicon negative electrode material (denoted as Si@SiNx / TiN) prepared in Example 1; Figure 4 This is an XPS graph of the micron silicon negative electrode material (denoted as Si@SiNx / TiN) prepared in Example 1; Figure 5 This is a SEM image of the micron silicon negative electrode material prepared in Comparative Example 1; Figure 6 This is a SEM image of the micron silicon negative electrode material prepared in Comparative Example 2; Figure 7 This is a SEM image of the micron silicon negative electrode material prepared in Comparative Example 3; Figure 8 The charge and discharge curve of the micron silicon negative electrode material prepared in Example 1 as the negative electrode active material of a lithium ion battery in a half-cell (100 mA g -1 ), Fig. 9 Cyclic performance diagram of the micron silicon negative electrode material prepared in Example 1 as a negative electrode active material for lithium-ion batteries in a half-cell (100 mA g -1 ); Fig.10 Cyclic performance diagram of the micron silicon negative electrode material prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 as the negative electrode active material of lithium ion batteries in half cells (200 mA g -1 ); Fig.11 The rate performance diagram of the micron silicon negative electrode material prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 as the negative electrode active material of the lithium ion battery in the half-cell; Fig.12 The cycle performance diagram (1C) of the micron silicon negative electrode material prepared in Example 1 as the negative electrode active material of a lithium ion battery in a full battery with LiFePO4 as the positive electrode; Fig.13 This is a rate performance diagram of the micron silicon negative electrode material prepared in Example 1 as a negative electrode active material for a lithium-ion battery in a full battery with LiFePO4 as the positive electrode. DETAILED DESCRIPTION

[0018] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.

[0019] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0020] Example 1 The method for preparing the nitrided modified micron silicon negative electrode material comprises the following steps: (1) Weigh 500 mg of micronized silicon and 100 mg of titanium nitride, put them into a beaker, add 100 mL of ethanol, ultrasonicate for 30 min, and stir for 1 h to obtain a uniform suspension; (2) placing the suspension obtained in step (1) in an oven at 80°C for 24 h to obtain a uniformly mixed powder; (3) The mixed powder obtained in step (2) was placed in a corundum furnace and reacted at 1300°C for 5 min in a nitrogen atmosphere to obtain a micron silicon negative electrode material.

[0021] Example 2 The present invention provides a method for preparing a nitrided modified micron silicon negative electrode material, which is basically the same as that of Example 1, except that in step (3), the nitridation temperature is 1200°C.

[0022] Example 3 The present invention provides a method for preparing a nitrided modified micron silicon negative electrode material, which is basically the same as that of Example 1, except that in step (3), the nitridation temperature is 1400°C.

[0023] Example 4 The present invention provides a method for preparing a nitrided modified micron silicon negative electrode material, which is basically the same as that of Example 1, except that: in step (3), the nitridation time is 1 min.

[0024] Example 5 The present invention provides a method for preparing a nitrided modified micron silicon negative electrode material, which is basically the same as that of Example 1, except that: in step (3), the nitridation time is 15 min.

[0025] Example 6 The present invention provides a method for preparing a nitrided modified micron silicon negative electrode material, which is basically the same as that of Example 1, except that: in step (3), the nitridation time is 30 min.

[0026] Comparative Example 1 The present invention provides a method for preparing a nitrided modified micron silicon negative electrode material. The comparative example is basically the same as Example 1, except that the micron silicon is directly calcined in a nitrogen atmosphere. The sample is recorded as Si@SiNx. The SEM image is as follows Figure 5 shown.

[0027] Comparative Example 2 The present invention provides a method for preparing a nitrided modified micron silicon negative electrode material. The comparative example is basically the same as Example 1, except that the micron silicon and titanium nitride powders after being uniformly mixed are not subjected to high temperature calcination treatment, which is recorded as Si / TiN. The SEM image is as follows: Figure 6 As shown, the micron silicon particles and titanium nitride particles are obviously in a mechanically mixed state.

[0028] Comparative Example 3 The present invention provides a method for preparing a nitrided modified micron silicon negative electrode material. The comparative example is original micron silicon, the sample is denoted as Si, and the SEM image is as follows: Figure 7 As shown, the average size is 1-3 um.

[0029] The SEM image of the micron silicon negative electrode material (denoted as Si@SiNx / TiN) prepared in Example 1 is as follows: Figure 1 As shown, it can be seen that the surface of the material is dense and smooth.

[0030] The TEM and EDX images of the micron silicon negative electrode material (denoted as Si@SiNx / TiN) prepared in Example 1 are as follows: Figure 2 As shown, it can be seen that both the nano-titanium nitride particles and the micron-silicon particles are completely covered under the amorphous silicon nitride layer.

[0031] The XRD image of the micron silicon negative electrode material (denoted as Si@SiNx / TiN) prepared in Example 1 is as follows: Figure 3 As shown, the prepared silicon nitride has no obvious characteristic peaks and is therefore amorphous silicon nitride.

[0032] The XPS image of the micron silicon negative electrode material (denoted as Si@SiNx / TiN) prepared in Example 1 is as follows: Figure 4 As shown, the corresponding Si 2p and N 1s peaks of silicon nitride can be seen.

[0033] The materials prepared in Examples 1-3 were subjected to electron microscopy and XRD characterization, and the measurement results are shown in Table 1. Table 1 Silicon nitride prepared by calcining at different temperatures for 5 min.

[0034]

[0035] From Table 1, we can see that the coating thickness of the material treated at 1300℃ is appropriate and the silicon nitride is amorphous. This is because the temperature condition for the rapid reaction of elemental silicon and nitrogen to generate silicon nitride is 1300℃. At 1200℃, the reaction degree of silicon and nitrogen is very low, and it is impossible to prepare an ideal silicon nitride coating. When the temperature rises to 1400, due to the high temperature, silicon and nitrogen react rapidly to generate silicon nitride and crystallize. Crystalline silicon nitride has almost no chemical activity, which seriously hinders the diffusion of lithium ions into the internal silicon elemental material and is not suitable as a coating for silicon negative electrodes. Therefore, the ideal temperature for preparing amorphous silicon nitride is 1300℃.

[0036] The micron silicon negative electrode materials Si@SiNx / TiN prepared in Example 1, Example 4, Example 5, and Example 6 were assembled as negative electrode active materials in lithium ion half-cells, and electrochemical performance tests were performed (large current specific capacity was measured at a current density of 1 A / g, and other indicators were measured at a current density of 0.1 A / g). The results are shown in Table 2. Table 2 shows the electrochemical performance indicators of the materials after calcination at 1300°C for different times:

[0037] From Table 2, we can see that the shorter the nitridation time is, the higher the first discharge capacity and high current capacity of the battery can be. However, the first coulombic efficiency and capacity retention rate of the material are relatively low. This is because the heat treatment time is too short and the content of silicon nitride formed is relatively small. As time goes on, both the first discharge capacity and high current capacity, as well as the first coulombic efficiency and capacity retention rate, become smaller with the increase of heat treatment time. The reason may be that the heat treatment time is too long, the silicon nitride content generated is too much, and the coating layer is too thick, which seriously hinders the diffusion of lithium ions into the internal silicon single material. Therefore, the ideal time for preparing amorphous silicon nitride is 5 minutes.

[0038] The micron silicon negative electrode materials Si@SiNx / TiN, Si@SiNx, Si / TiN, and Si prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are assembled in lithium-ion half cells as negative electrode active materials.

[0039] Figure 8 The charge and discharge curves of Si@SiNx / TiN in a half-cell are shown (discharge current is 100 mA g -1 ), it can be seen that the first coulombic efficiency of the battery is 85.37%, which has a high first coulombic efficiency.

[0040] Fig. 9 The cycling performance of Si@SiNx / TiN in a half-cell (discharge current 100 mA g -1 ), it can be seen that the capacity retention rate of the battery after 100 cycles is 86.0%, which has a high capacity retention rate.

[0041] like Fig.10 The figure shows the cycle performance of four micron silicon negative electrode materials, Si@SiNx / TiN, Si@SiNx, Si / TiN, and Si in half-cell (discharge current is 200 mA g -1 ), it can be seen that Si@SiNx / TiN has excellent cycle stability.

[0042] like Fig.11 Shown is the rate performance diagram of four micron silicon negative electrode materials, Si@SiNx / TiN, Si@SiNx, Si / TiN, and Si in half-cells. It can be seen that Si@SiNx / TiN still has excellent rate performance.

[0043] The present invention adopts a method for surface nitriding treatment of micron silicon particles and nano titanium nitride particles, and prepares amorphous silicon nitride on the surface of the material by controlling the reaction temperature and time. The amorphous silicon nitride is prepared using nitrogen, and the surface properties of the micron silicon are improved, which greatly improves the stability of the SEI film. The added titanium nitride can maintain structural stability at high temperatures, provide good electrical conductivity for the silicon negative electrode, and provide a new idea for the modification and preparation of micron silicon negative electrode materials. Since the raw material is micron-sized silicon particles, the cost can be greatly reduced, and the volumetric capacity of the electrode can be improved, which is more practical.

[0044] To further verify the electrochemical performance of the material, the micron silicon negative electrode material Si@SiNx / TiN prepared in Example 1 was used as the negative electrode active material in a lithium-ion full battery. The positive electrode active material was LiFePO4, and its full battery cycle performance diagram (0.2 C) is shown in Fig.12 As shown, its excellent cycle performance can be seen; its full battery rate performance is shown in Fig.13 As shown, its excellent rate performance can be seen.

[0045] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A nitride-modified silicon negative electrode material, characterized in that: The silicon negative electrode material comprises micron silicon particles and nano titanium nitride particles distributed on the surface of the micron silicon particles, and the surfaces of the micron silicon particles and the nano titanium nitride particles are both coated with an amorphous silicon nitride layer.

2. The nitride-modified silicon negative electrode material according to claim 1, characterized in that: The particle size of the micron silicon particles is 1-3 um, and the particle size of the titanium nitride particles is 5-30 nm.

3. The nitride-modified silicon negative electrode material according to claim 1, characterized in that: The thickness of the amorphous silicon nitride layer is 5-25 nm.

4. A method for preparing a nitride-modified silicon negative electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Take micron silicon particles and titanium nitride particles and add them to a solvent for ultrasonic dispersion, and then stir them to make them evenly dispersed to obtain a uniform suspension. 2) Dry the suspension to obtain micron silicon / titanium nitride mixed powder. 3) The mixed powder is placed in a tubular furnace and calcined at high temperature in a nitrogen atmosphere to obtain silicon@silicon nitride / titanium nitride material, that is, a nitride-modified silicon negative electrode material.

5. The preparation method according to claim 4, characterized in that: In the step 1), the mass ratio of the micron silicon particles to the titanium nitride particles is 5:

1.

6. The preparation method according to claim 4, characterized in that: In the step 1), the solvent is one or more of water, methanol, ethanol and NMP.

7. The preparation method according to claim 4, characterized in that: In the step 1), the ultrasonication time is 20 min-60 min, and the stirring time is 0.5 h-2 h.

8. The preparation method according to claim 4, characterized in that In the step 3), the high temperature calcination temperature is 1200-1400°C, more preferably 1300°C; the high temperature calcination time is 1-30 min, more preferably 5 min.

9. The preparation method according to claim 4, characterized in that: In the step 2), the drying temperature is 80-120° C. and the drying time is 20-30 hours.

10. Use of the silicon negative electrode material according to claims 1-3 or the silicon negative electrode material prepared by the method according to claims 4-9 in lithium ion batteries.

Citation Information

Patent Citations

  • Preparation method of C-SiC-Si composite negative electrode material for lithium ion battery

    CN115377399A

  • Preparing method for carbon nanofibers composites comprising silicon / silicon nitride and silicon carbide core-shell composites

    KR1020170130786A

  • KR20240088002A